THE USE OF ONLINE VIDEO SIMULATION ON STUDENT’S COMPETENCE, MOTIVATION AND ANXIETY LEVEL - Erna Rochmawati; Fahni Haris; Resti Yulianti Sutrisno; Wulan Noviani (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Nursing student often experience anxiety and lack of motivation during their training program particularly during examination, and this may affect the achievement of learning outcomes. Teaching methods that might increase motivation and potentially increase learning outcomes have been developed, including video simulation and online learning. The purpose of the study was to investigate the effects of integrating video simulation into online learning on students’ motivation, anxiety level and competence. Methods: A pre-test/post-test one group design was utilized. Two video simulations containing nursing skills were integrated into the e-learning system which can be accessed for three weeks by 76 respondents who took Basic Nursing course. The level of motivation and anxiety were measured before and after the intervention, while the competence was measured after the intervention. Results: The majority of students passed the skills examination. This study indicates a significant increase of students’ motivation after the intervention (p value < 0.001), but the level of anxiety among respondents increased. Conclusion: The integration of video simulation into e-learning system can enhance student’s skills performance and motivation. Although there is also an increase in anxiety, findings of the study can be applied to other subjects and nursing skills with attention to aspects that cause student anxiety.